2019
DOI: 10.1107/s2052520619006528
|View full text |Cite
|
Sign up to set email alerts
|

The structure and crystal chemistry of vernadite in ferromanganese crusts

Abstract: The structure and crystal chemistry of vernadite in ferromanganese crusts from the Magellan Seamount in the north-west Pacific Ocean have been investigated using synchrotron X-ray diffraction (XRD), X-ray pair distribution function (PDF) and high-resolution transmission electron microscopy (TEM). XRD patterns of vernadite mainly show two strong diffraction peaks at 2.42-2.43 Å and 1.41 Å without or with a broad (001) diffraction peak, indicating thin layer nanophases along the c-direction. TEM images show flat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 49 publications
3
37
0
Order By: Relevance
“…Vernadite is found in the oxidized zone of Mn-rich deposits and might be a major phase in ocean Mn nodules and crusts (Chukrov et al 1987). Vernadite often is assumed to be analogous to the synthetic phase δ-MnO 2 (Villalobos et al 2003;Grangeon, 2010;Lee et al 2019), although the term δ-MnO 2 has been applied very broadly in recent years. Some have suggested that its formation is primarily mediated by biota (Chukrov et al 1987;Grangeon et al 2012).…”
Section: Vernaditementioning
confidence: 99%
See 2 more Smart Citations
“…Vernadite is found in the oxidized zone of Mn-rich deposits and might be a major phase in ocean Mn nodules and crusts (Chukrov et al 1987). Vernadite often is assumed to be analogous to the synthetic phase δ-MnO 2 (Villalobos et al 2003;Grangeon, 2010;Lee et al 2019), although the term δ-MnO 2 has been applied very broadly in recent years. Some have suggested that its formation is primarily mediated by biota (Chukrov et al 1987;Grangeon et al 2012).…”
Section: Vernaditementioning
confidence: 99%
“…Webb, 2005). Others use pair distribution function modeling to assess the symmetry and other structural details (Yang et al 2019;Lee et al 2019). A drawback of both approaches is that data must be collected using synchrotron sources.…”
Section: Birnessite Symmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of Mn oxides were observed in the Fe-Mn crusts of RGR. The first has no basal reflection and diagnostic reflections at 2.45 Å and 1.42 Å, which correspond to the disordered phyllomanganate vernadite [36,37], also termed Fe-vernadite by some authors because it corresponds to Vernadite epitaxially intergrown with amorphous FeOOH [35,38,39]. The second has basal reflections at 10 Å and 5 Å and possible reflections overlapping with those of Vernadite at 2.45 Å and 1.42 Å peaks, which are together characteristic of 10 Å phyllomanganates, which can be either disordered 10 Å vernadite, or ordered buserite or asbolane, or a mixture of them [35,[40][41][42][43].…”
Section: Mineralogymentioning
confidence: 99%
“…To investigate this, we performed Rietveld analysis of a series of powder diffraction patterns collected from 300-1100 K in which the isotropic atomic displacement parameters (ADPs) of the inequivalent Bi sites were independently rened (4 in a, 5 in b, 1 in g). The ADPs can provide valuable structural information, [31][32][33] and while this analysis pushes the information content of powder diffraction to its limits, we nd that the Bi4 and Bi5 atoms, which disorder during the phase transition, have ADPs in the b phase comparable to those in g-Bi 2 Sn 2 O 7 and much larger than the other Bi atoms (Fig. S12 †).…”
Section: Distorting the Cubic Aristotypementioning
confidence: 89%